Respostas de duas espécies de macrófitas do gênero Polygonum à flutuação dos níveis de água e à competição interespecífica. - Murillo, Raytha de Assis (2018)
Water level fluctuations are common in aquatic environments and may influence directly or indirectly the spatial distribution of emergent macrophytes, causing a pattern of zonation. The most important mechanisms that determine this species zonation are their ability to tolerate environmental stressors, such as inundation, and their competitive interaction, which may vary in magnitude in an environmental gradient. In this study, we assessed the zonation of two species of emergent macrophytes, Polygonum ferrugineum and Polygonum acuminatum, as well as the mechanisms of their distribution by combining observational and experimental approaches. We modeled historical abundance data of 16 years collected from the Upper Rio Paraná Floodplain in function of depth using a Bayesian approach. Then, we designed a factorial experiment in blocks, where shoot fragments of each species were planted and grown in constant density in monocultures and mixtures and submitted to three water level treatments – low, high and variable (Ldep, Hdep and Vdep) for 30 days. All the measured response variables and relative yields (RY) were analyzed with a two-way ANOVA. The observational data showed that both species colonize different depths, evidencing zonation, in which P. acuminatum colonizes shallower areas than P. ferrugineum. Regarding the monocultures, there were no differences in biomass accumulation from either species. However, P. acuminatum showed a significant elongation of its shoot and internodes when it was grown in submersion treatments (Hdep and Vdep). This result is indicative of differential survival strategies between the two species, in which P. acuminatum resists inundation through an escape strategy, by elongating its shoot above the water surface, while P. ferrugineum showed a quiescence strategy by drastically reducing its growth rates and tolerating inundation temporarily. Regarding the mixtures, there were no difference in RY among the different treatments, indicative that water level fluctuations do not influence the magnitude of competition between these species. However, P. acuminatum showed a marginally significant advantage over P. ferrugineum, indicating that in favorable conditions, such as in constantly shallow habitats, this species might outcompete P. ferrugineum. These results are consistent with the observational results, because they show that P. acuminatum can dominate shallower areas of the littoral zone by having both morphological adaptations to intermittent fluctuations in water level and competitive advantage over P. ferrugineum. On the other hand, P. ferrugineum is limited to deeper areas, where it can tolerate inundation until favorable conditions occur. Once established it is capable of growing plagiotropic branches above the water column and colonize deeper areas than P. acuminatum.